Relasi Intelektualitas dan Spiritualitas Perspektif Tarekat Naqsabandiyah Khalidiyah - Maulani, Maulani; Rabbani, Nidal; Wasik, Abdul (Jurnal Penelitian Ilmu Ushuluddin, 2025)
The integration between intellectuality and spirituality in Sufism is very necessary because it can produce self-actualization for followers of tarekat, so that human behavior will reflect divine traits in their daily lives. This study aims to examine the relationship between intellectuality and spirituality which then has an impact on the morality of the congregation of the Naqsabandiyah Khalidiyah tariqah perspective. This research uses a qualitative method conducted at the Prof. Dr. Kadirun Yahya Foundation located on Jenderal Gatot Subroto Street KM 4.5 Sei Siskamling Medan, North Sumatra. This study found that in the study of Naqsabandiyah Khalidiyah tarekat pioneered by Shaykh Kadirun Yahya, self-actualization or ihsan behavior in Sufism can be obtained through a process of integration between intellectual and spiritual potential. This is done because every congregation of the congregation must have an understanding and ability to explain the scientific concepts of the implementation of spiritual rituals performed. The scientific tradition built by Sheikh Kadirun Yahya in Tarekat Naqsabandiyah Khalidiyah is intended to encourage the intellectual potential of the congregation, considering that theories related to general sciences such as natural science, physics, and chemistry are growing rapidly. Meanwhile, religious sciences seem to have developed rapidly, but have stagnated due to religious teachings that are adhered to traditionally and dogmatically. Future research is expected to further analyze the contribution of Shaykh Kadirun Yahya's thought to the renewal of the Sufism tradition in a modern context, especially amid the challenges of globalization and secularization.